Translation in language teaching, pedagogical translation, and code-Switching: restructuring the boundaries. Issue 2 (4th March 2021) - Pintado Gutiérrez, Lucía
ABSTRACT: The gradual reintroduction of translation into the foreign language classroom in the last few decades has generated considerable interest among teachers and scholars. A renewed focus on translation as an aspect of language teaching has simultaneously originated from and resulted in the publication of theoretical and empirical studies as well as monographs that recognise 'pedagogical translation' as a beneficial and increasingly accepted practice. However, conceptual and terminological inconsistencies persist that blur the boundaries between the general idea of using translation in the language classroom and more specific practices that involve translation tasks (also known as 'pedagogical translation') or code-switching. The article addresses these terminological incongruities by exploring the impact of conceptualisations of translation in language education and, specifically, its use in pedagogical translation. The goal is to consider the plethora of concepts related to translation in language teaching (TILT) and to explore how they may be connected with the reconceptualisation of translation in language pedagogy. This will open up useful avenues for a more thorough incorporation of translation into foreign language education, particularly at the secondary and college level, and will propose future lines of research and pedagogical sound praxis.